MODERNISING THE DAYAH - Ismet Nur (IAIN Tulungagung, 2019)
The Acehenese Islamic educational institution, dayah, has played a major role in institutionalisation of Islam among the Acehness. As a traditional institution, the dayah system has developed and successfully translated principles of modernity through the establishment an integrated educational system. This article examines the modernization of Darul Mukhlisin in Central Aceh and its characteristic in modernising its educational system. The modernization of the education system is characterized by changes in the aspects of objectives, Teungku and the students (santri) of dayah, implementation of an integrated curriculum, the treasury of contemporary books, use of active strategies and varieties of educational methods, environmental changes, the application of test and non-test evaluation types, and so forth. This article further argues that the Darul Mukhlisin has been successfully adopting the dayah system into modern principles of modern management in educational institution. The Darul Mukhlisin resorts as an important agent for religious education, producing learned Muslims who contributes to the development of the Acehness.